Behavior Generation Millennials in Use Go-Food Application - Besse Miftahul Khaerina; Wulandari .B; Nur Sasatri Putri; Muhammad Hasan (PT FORMOSA CENDEKIA GLOBAL, 2023)
In the era of revolution industry fourth, progress technology information has change style life today 's generation, especially generation born millennials _ between 1980 to 2000. Generation _ millennial identify characteristic features what's unique is: 1) user content creation (UGC), 2) technology and literacy information, 3) consumer behavior and 4) tendencies lazy. In study This technique analysis descriptive And linear regression is used For data analysis . In the era of revolution industry fourth, importance development technology information will bring change fundamental in style life public everyday, Wu & Chiu (2015). Development This have impact direct and no directly towards method public Work And life. Change This push modern society towards consumerism. Millennials, too known as Generation Y, includes people born between 1980 and 2000 and _ aged around 15 to 34 years oldPg This in accordance with Average age of students : between 19 and 34 years